Development of expert project management system (EPMS) in Android / Che Mohamad Anis Che Mat - Che Mat, Che Mohamad Anis (2013)
Expert Project Management System or EPMS developed to apply the latest technology of android into the project management system. In the previous system that has been developed, it is became a problem as it is developed under windows system or a web-based system that running on a laptop or pc. The size of the device itself has making a burden for them to carry a laptop to any project site to ensure they can check project progress. Another problem that been face by user is the difficulties to track down each cost that has been used for the project. By having Expert Project Management System, project manager can use the software using their android mobile device. This way project manager can bring the software and use anywhere without any difficulties as it is in a size that is small enough for them to use. By having Expert Project Management System also, project manager can track the budget that has been use for the project easily and can save them from excessing the budget. There are three objective that must be achieved in the project. The first objective is to develop android based application on the project management system. The second objective is to develop function to keep track of the progress and cost and the third objective is to create final assessment on the project based on the project progress. The development of Expert Project Management System is based on Rapid Application Development as it allow fast implementation of the system in real environment. The development start with Analysis and quick design and move on to prototype circles where develop, demonstrate and refine happen. It then procedd to testing and deployment.